Improving Students' Language Skills with Punakawan Wayang Media at RA Mansyaul Huda: A Classroom Action Research - Latifah, Ifa; Safrida, Ida (Journal of Indonesian Primary School, 2025)
The research objectives to be achieved in this study are to describe the language skills of early childhood children as well as teacher performance through Punakawan puppet media in group A at RA Mansyaul Huda. Classroom Action Research using 2 cycles, each cycle consists of planning, implementation, observation and reflection stages. The subjects of this study were group A RA Mansyaul Huda which consisted of 12 children. Data were obtained through observation, documentation, and portfolios. Data analysis used descriptive percentage analysis. Conclusion: the results of the study are that children's language development in cycle I conditions in the category of developing according to expectations (BSH), has increased from the pre-cycle condition, namely 2 (two) children with a percentage of 17% to 3 (three) children with a percentage of 25%. The category of developing very well (BSB) from pre-cycle 1 (one) child to 2 (children) cycle I. While the data on children who are starting to develop (MB) in pre-cycle 2 (children) conditions with a percentage of 17% to cycle I is still the same 2 (two) children. The results in cycle II showed that there were no more data on children who were still not developing (BB). Meanwhile, there were 4 (four) children who had started to develop (MB) in their language development or with a percentage of 33.4%. The language development ability expected by the teacher in the conditions of cycle II in the category of developing according to teacher expectations (BSH) had increased to 7 (seven) children from the first and second meeting activities or with a percentage of 58.3%. Meanwhile, the data obtained for children who were developing very well (BSB) were 3 (children) with a percentage of 25%. The teacher's performance in the learning process carried out in cycle I, activity 1, the number of scores obtained was good, then increased in activity 2 to cycle 2, namely with a very good value.